2014
DOI: 10.1002/jat.3053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and predictive performance and standardized threshold of traditional biomarkers for drug‐induced liver injury in rats

Abstract: Traditional biomarkers such as alanine and aspartate aminotransferase (ALT, AST) and total bilirubin (TBIL) have been widely used for detecting drug-induced liver injury (DILI). Although the Food and Drug Administration (FDA) proposed standardized thresholds for human as Hy's law, those for animals have not been determined, and predictability of these biomarkers for future onset of hepatic lesions remains unclear. In this study, we investigated these diagnostic and predictive performance of 10 traditional biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This increased effect was in accordance with other studies. For instance, studies have shown that ALT is more specific for liver than AST as the later was also seen in muscle damage 14,15 .…”
Section: Fig 8a and B: Electromicrographs Of Rat Liver Of Group IV Smentioning
confidence: 99%
See 1 more Smart Citation
“…This increased effect was in accordance with other studies. For instance, studies have shown that ALT is more specific for liver than AST as the later was also seen in muscle damage 14,15 .…”
Section: Fig 8a and B: Electromicrographs Of Rat Liver Of Group IV Smentioning
confidence: 99%
“…For example, increased levels of liver enzymes, alanine and aspartate aminotransferases (ALT and AST, respectively), widely used serum biomarkers for liver toxicity 13 . Studies have shown that ALT is more specific for liver than AST as the later was also seen in muscle damage 14,15 . Remedies of herbal extracts have been used to reduce the adverse effects and protect against drug liver toxicity, and they have been used at preclinical and clinical levels 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Alanine and aspartate aminotransferase (ALT and AST), alkaline phosphatase (ALP), total bilirubin (TBIL) and γ-glutamyltransferase (GGT) are considered the reference biomarkers and are widely employed for the detection of DILI, providing supporting information in pre-clinical and clinical toxicity studies for drug development (US FDA, 2009; Tonomura et al, 2015). However, they are not always specific and sensitive in recognizing liver diseases provoked by DILI or other causes such as viruses (Przybylak and Cronin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional biomarkers used in preclinical drug development include proteins such as albumin, aspartate aminotransferase, and alkaline phosphatase and metabolites such as bilirubin, creatinine, and triglycerides 5 . Although these biomarkers can effectively diagnose DILI, traditional biomarkers are limited in scope to accurately predict future onset of DILI 6 . High-throughput metabolomics methods have the potential to significantly improve both diagnostic and predictive biomarkers of DILI by expanding the potential pool of biomarkers from a few dozen to thousands of metabolites [7][8][9] .…”
Section: Background and Significancementioning
confidence: 99%
“…High-throughput metabolomics methods have the potential to significantly improve both diagnostic and predictive biomarkers of DILI by expanding the potential pool of biomarkers from a few dozen to thousands of metabolites [7][8][9] . In contrast to biomarkers like aspartate aminotransferase, which are released into the blood after hepatocellular membrane disintegration 6 , we anticipate that metabolite biomarkers will require less catastrophic perturbations to be detected and will be more sensitive to the direct mechanisms of hepatocyte injury 6 . Preclinical efforts to identify biomarkers associated with toxicity typically use statistical methods that correlate changes in metabolite concentrations with toxicant exposure [7][8][9][10][11][12][13] .…”
Section: Background and Significancementioning
confidence: 99%